Sequencing of idiopathic pulmonary fibrosis-related genes reveals independent single gene associations. Issue 1 (10th December 2014) - Coghlan, Meghan A; Shifren, Adrian; Huang, Howard J; Russell, Tonya D; Mitra, Robi D; Zhang, Qunyuan; Wegner, Daniel J; Cole, F Sessions; Hamvas, Aaron
Abstract : Background: Previous studies investigating a genetic basis for idiopathic pulmonary fibrosis (IPF) have focused on resequencing single genes in IPF kindreds or cohorts to determine the genetic contributions to IPF. None has investigated interactions among the candidate genes. Objective: To compare the frequencies and interactions of mutations in six IPF-associated genes in a cohort of 132 individuals with IPF with those of a disease-control cohort of 192 individuals with chronic obstructive pulmonary disease (COPD) and the population represented in the Exome Variant Server. Methods: We resequenced the genes encoding surfactant proteins A2 ( SFTPA2 ), and C ( SFTPC ), the ATP binding cassette member A3 ( ABCA3 ), telomerase ( TERT ), thyroid transcription factor ( NKX2-1 ) and mucin 5B ( MUC5B ) and compared the collapsed frequencies of rare (minor allele frequency <1%), computationally predicted deleterious variants in each cohort. We also genotyped a common MUC5B promoter variant that is over-represented in individuals with IPF. Results: We found 15 mutations in 14 individuals (11%) in the IPF cohort: ( SFTPA2 (n=1), SFTPC (n=5), ABCA3 (n=4) and TERT (n=5)). No individual with IPF had two different mutations, but one individual with IPF was homozygous for p.E292V, the most common ABCA3 disease-causing variant. We did not detect an interaction between any of the mutations and the MUC5B promoter variant. Conclusions: Rare mutations in SFTPA2, SFTPC and TERT are collectively over-represented in individuals with IPF. Genetic analysis and counselling should be considered as part of the IPF evaluation.